Isolation and Physiomorphological Characterization of Escherichia coli O157:H7-Infecting Bacteriophages Recovered from Beef Cattle Operations - Pushpinder Kaur Litt; Divya Jaroni (International Journal of Microbiology)
Bacteriophages, recovered from beef cattle environment and specifically targeting Escherichia coli O157:H7, were examined for their physiological and morphological characteristics. Degree of bacterial lysis and host range of isolated bacteriophages was determined against 55 isolates of E. coli O157:H7. Morphology of phages was examined under transmission electron microscope. Phage growth parameters, particularly rate of adsorption, rise period, latent period, and burst size were also determined. The stability of isolated phages was tested at acidic and alkaline pH, at high temperatures, and in cold storage. A total of 7 phages were isolated which showed lytic activity against 50 out of 55 isolates of E. coli O157:H7. Based on the morphology, phages were classified into Myoviridae or Siphoviridae family. Phages had a rise period between 19 and 40 min, a short latent period between 12 and 30 min, and a large burst size (89–631 virions per infected cell), indicating high lytic activity. Phages remained stable for 24 h at a wide pH (1–11) and temperature range (40–60°C) and for 90 d in cold storage. Characterization of bacteriophages, with a diverse host range of E. coli O157:H7, could aid in the development of effective biocontrol strategies for this pathogen in the food industry.